Evaluating the Efficacy and Trend of Sinus Surgery - Petrovic,Masa (2020)
Abstract Introduction From April 2009 to December 2016, 661 consecutive patients undergoing sinus surgery completed a quality of life (QOL) questionnaire (SNOT-22) preoperatively and at 3, 6, and 12 months postoperatively. Objective (1) To evaluate the long-term efficacy of sinus surgery using QOL instruments. (2) To determine the optimal evaluation time for surgical efficacy. (3) To determine if surgical results improve with yearly experience. Methods The prospective study patients were split into two groups: Group A, those who completed the initial preoperative evaluation and all postoperative evaluations, and Group B, who completed the preoperative questionnaire and at least one but not all of the postoperative questionnaires. Group A included 93 patients. Group B included 240 patients at 3 months, 180 at 6 months, and 121 at 12 months postoperatively. Results Group A efficacy reported at 3 months was 82.8%, 80.6% at 6 months, and 84.9% at 12 months postoperatively. Group B efficacy reported at 3 months was 71.3%, 78.3% at 6 months, and 84.3% at 12 months postoperatively. An 8-year trend analysis of year-to-year 12 months postoperative data illustrates a significant improvement with an analysis of variance (ANOVA) linear rate of 1.594 (p≤0.12). Conclusion The 8-year trend at 12 months postoperatively shows a positive improvement in surgical results. Patients undergoing sinus surgery at tertiary medical center showed 84.9% improvement in sinus disease symptoms by 12 months postoperatively. Long-term improvement analysis showed no difference between 6 months postoperatively and 12 months, signifying 6 months as an effective evaluation for surgical efficacy.